Pariwisata Dalam Meningkatkan Kunjungan Destinasi Wisata Di Provinsi Sulawesi Selatan - Fadillah, Ikhsan; Mone, Ansari; Riskasari, Riskasari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aimed to determine the promotion strategy of the Culture and Tourism Office in increasing tourist destination visits in South Sulawesi Province. This study used  qualitative research, while the informants were 4 people. Data collection techniques were in-depth interviews with a number of informants., Direct observation, documentation. The results of this study showed that the lack of socialization by the government to farmers about the importance of farmer groups, as well as the provision of counseling, understanding in socializing the problem. This could be seen from the indicators: (1) Identification of target audience: The Office of Culture and Tourism in determining the target audience did not use certain techniques, to reach tourists widely the determination was only done from market analysis, (2) message design of the Culture and Tourism Department in designing messages i.e. the use of sentences based on the beauty of each tourist attraction in each region, and (3) the selection of media used was based on the availability of print media funds such as brochures, posters, billboards, phamplets, and stickers while for online media namely websites and social media attending events  were also carried out by showing video documentaries about attractions.Keywords: Tourism, Increased Visit Destinations